Global subnational estimates of migration of scientists reveal large disparities in internal and international flows - Aliakbar Akbaritabar; Maciej J. Dańko; Xinyi Zhao; Emilio Zagheni (Proceedings of the National Academy of Sciences, 2025)
Researchers are key contributors to innovation. Their migration results in talent circulation and recombination of ideas. Due to data shortage, little is known about subnational mobility of scientists and the interrelationships between their internal and international migration patterns. We used data on 30+ million Scopus publications of 19+ million authors to infer migration from changes in affiliations. Our publicly shared database of global subnational estimates of migration reveals relevant disparities in the attractiveness of subnational regions. While, at the country level, some countries have acted as a global hub that attracts scholars from throughout the world, at the subnational level, some of their regions have negative net migration rates, with implications for scientific output and regional development, as well as the perpetuation of migration corridors. On average, subnational inequalities in attracting and sending scholars have increased for international but decreased for internal migration. In most countries, there is no single trend such that all subnational regions have been sending or receiving more scholars. Instead, a mix of patterns has been simultaneously at work, on the backdrop of globalization of migration, which is an asymmetric process where specific regions and subpopulations have higher access to international migration. For most subnational regions, when they are attractive for international migrants, they are also attractive for internal migrants, which is not always the case for emigration. Our results have implications for the global circulation of academic talent by adding the dimension of internal migration to “brain drain” and “brain circulation” in international migration.